Pengaruh Penerapan Pembelajaran PBL Berbantuan Alat Peraga terhadap Hasil Belajar IPA Siswa Kelas IV SDN 21 Lubuk Lintah Kota Padang: The Effect of Implementing PBL Learning Assisted by Teaching Aids on Science Learning Outcomes for Class IV Students at SDN 21 Lubuk Leech, Padang City - Muliani, Desy Eka (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research is motivated by deficiencies in the science learning process. It is known that the dominant teaching method used is lecture, which minimally involves students in active learning. As a result, students are not given extensive opportunities to independently find solutions to problems or understand the concepts presented. This research aims to determine the impact of implementing Problem Based Learning (PBL) assisted by teaching aids on the science learning outcomes of class IV students. This research method uses a Quasi-Experimental design, specifically using a posttest-only control design. The experiment was carried out by comparing the posttest results of students who experienced the PBL model with those who did not. The research results through data analysis using the t test produced a t value of 2.52 and a t table value of 1.682. This shows that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that there is a significant influence of the use of the PBL model assisted by teaching aids on the science learning outcomes of class IV students at SDN 21 Lubuk Lintah, Padang City.